Exercise training in pulmonary rehabilitation: are functional exercises and elastic resistance training effective strategies? - Lima, Fabiano Francisco de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
A key priority in Pulmonary Rehabilitation (PR) programs is to increase their accessibility. Elastic resistance training stands out for its low cost, practicality, and portability, allowing people to perform resistance training in their home environment. Lemgruber® Elastic tubing (LET) has been proposed as a tool for such an end. Exercise training in PR programs commonly involves aerobic and resistance training, showing clinically relevant results when combined. PR programs provide significant functional gains for patients with Chronic Obstructive Pulmonary Disease (COPD). The evidence for increasing physical activity in daily life (PADL) with PR is contradictory and inconsistent. It is suggested an small effect on PADL with an inconsistent translation of functional gains into increased PADL. Functional exercise training can be a promising alternative. Objectives: This thesis presents the following objectives: To assess the length-resistance relation of elongation and resistance of five Lemgruber® elastic tubings (LET) of different diameters; Conduct a systematic review to investigate the effectiveness of elastic resistance training on improving muscle strength, functional exercise capacity, health-related quality of life (HRQoL) and dyspnea in patients with stable COPD; To evaluate the short term (8 weeks) and sustained effects (12 weeks post-training follow-up) of the combination of a functional exercise training, with a training program consisting of aerobic and resistance exercise in patients with COPD. Methods: Four studies were conducted to answer the objectives of this thesis and are presented as separated articles: 1) a descriptive laboratory study to evaluate the LET; 2) a systematic review and meta- analysis on the effectiveness of elastic resistance training in patients with COPD; 3) a study protocol and a randomized clinical trial on the effects of the combination of functional exercises with exercise training in patients with COPD. Results: The main viiifindings of this thesis were that the large array of resistances delivered by LET, along with its safety and reasonable estimation of reference values, support its use in clinical practice. Elastic resistance training is an effective intervention to improve muscle strength in patients with COPD. Further, compared to resistance training using weight machines, elastic resistance training demonstrated similar effects on muscle strength, functional exercise capacity, HRQoL and dyspnea. The inclusion of a functional exercise training protocol in training conventionally performed by patients with COPD could not improve the PADL and activities in daily living limitations.

Uma prioridade chave dos programas de Reabilitação Pulmonar (RP) é aumentar sua acessibilidade. O treinamento resistido elástico se destaca pelo baixo custo, praticidade e portabilidade, permitindo que as pessoas realizem o treinamento resistido no ambiente domiciliar. Os tubos elásticos Lemgruber® (LET) tem sido proposto como uma ferramenta para este fim. O treinamento físico em programas de RP geralmente envolve treinamento aeróbico e resistido, mostrando resultados clinicamente relevantes quando combinados. Os programas de RP fornecem ganhos funcionais significativos para pacientes com Doença Pulmonar Obstrutiva Crônica (DPOC), entretanto, as evidências para o aumento da atividade física na vida diária (AFVD) com RP são contraditórias e inconsistentes, sugerindo um pequeno efeito na AFVD com uma tradução inconsistente de ganhos funcionais em aumento de AFVD. O treinamento físico funcional pode ser uma alternativa promissora. Objetivos: Esta tese apresenta os seguintes objetivos: Avaliar a relação comprimento-resistência de alongamento e resistência de cinco tubos elásticos Lemgruber® (LET) de diferentes diâmetros; Conduzir uma revisão sistemática para investigar a eficácia do treinamento resistido elástico na melhora da força muscular, capacidade funcional de exercício, qualidade de vida relacionada à saúde (QVRS) e dispneia em pacientes com DPOC estável; Avaliar os efeitos de curto prazo (8 semanas) e sustentados (12 semanas de acompanhamento pós-treinamento) da combinação de um treinamento físico funcional, com um programa de treinamento composto por exercício aeróbico e resistido em pacientes com DPOC. Métodos: Quatro estudos foram realizados para responder aos objetivos desta tese e são apresentados como artigos separados: 1) um estudo laboratorial descritivo para avaliação dos LET; 2) uma revisão sistemática e meta-análise sobre a eficácia do treinamento utilizando xresistência elástica em pacientes com DPOC; 3) um protocolo de estudo e um ensaio clínico randomizado sobre os efeitos da combinação de exercícios funcionais com treinamento físico em pacientes com DPOC. Resultados: Os principais achados desta tese foram que a grande variedade de resistências fornecidas por LET, juntamente com sua segurança e estimativa razoável de valores de referência, suportam seu uso na prática clínica. O treinamento utilizando resistência elástica é uma intervenção eficaz para melhorar a força muscular em pacientes com DPOC. Além disso, em comparação ao treinamento resistido com aparelhos de musculação, o treinamento utilizando resistência elástica demonstrou efeitos semelhantes na força muscular, capacidade funcional de exercício, QVRS e dispneia. Por fim, a inclusão de um protocolo de treinamento físico funcional no treinamento convencionalmente realizado por pacientes com DPOC não não foi capaz de melhorar a AFVD e limitações nas atividades de vida diária.
Treinamento físico na reabilitação pulmonar: os exercícios funcionais e o treinamento resistido elástico são estratégias eficazes?
Keywords: Chronic obstructive pulmonary disease; Physical exercise; Physical activity; Doença pulmonar obstrutiva crônica; Exercício físico; Atividade física